Impact of Children's Presence on Police Responses to Domestic Violence Call Situations. (August 2023) - Hovey, Angela; Rye, BJ; George, Evan; Scott, Susan; Chambers, Lori
The link between children exposed to intimate partner violence (IPV) and child maltreatment is well established; however, less is known about the impact children's presence may have on domestic violence disputes. This study investigated the role of children's presence in IPV police calls using data ( N = 2709) from supplementary reports provided by an Ontario, Canada police force, one-third of which led to criminal charges ( n = 909). When children were present: charges were less likely to be laid; the accused's emotional state was more likely to be rated by police as calm and the accused was less likely to be identified as using alcohol and/or drugs at the time of the call; and victim support interventions were more likely to be offered and accepted. Findings were considered in the context of when charges were laid versus not laid. Implications for police and support service interventions were discussed.